The Consumption of Dietary Supplements among Gym Members in Amman, Jordan - Abu Yaman, Mai; Omar, Mohammed (Progress in Nutrition, 2022)
Background: Dietary supplements (DS) are considered as a major part of many athletes’ life. Objective: The aim of the study was to determine the prevalence of DS use among gym members in Amman, Jordan. Moreover, to determine their sources of information about DS, and assess their level of knowledge regarding the use of DS. Methods: A cross-sectional study was conducted using validated questionnaire among 397 gym members in the city of Amman, Jordan. The questionnaire included demographic data, use of DS, sources of information of DS, and personal knowledge and attitudes about DS. Results: The results of the study indicated that (146 participants, 36.8%) of participants were between 24–29 years old and that the prevalence of DS use was (70.8%) of the participants. Most of the study participants were found to obtain their information from sport coaches (37.4%), followed by nutritionist (24.2%) and health staffs (11.1%). Proteins were found to be the most single type of DS used through the users of DS (21.4 %), followed by vitamins (14.0 %). Pearson chi-square statistics revealed that gender was the only variable that make significant difference (p<0.05) regarding the type of DS and the source of information among users of DS. About two-third of the users of DS had sufficient information or knowledge regarding their supplements and nearly the same percentage pay attention to the nutrition facts of these supplements. Statistical analysis program SPSS (version 21) was used and statistical significance set at p-value <0.05. Conclusion: A large proportion of gym members in Amman use DS with a high percentage of proteins and vitamins among the most used DS. Coaches and nutritionists play a key role in counseling gym members about appropriate DS. Actually, gym members need more education programs to increase the percentage of members with high knowledge regarding DS.